О возможности получения оценок скорости и торможения метеороидов по базе фотографических изображений головных эхо-сигналов метеорной РЛС ХНУРЭ - Волощук, Ю. И.; Черкас, Ю. В. (ХНУРЭ, 2008)
The Photographic base of KTURE has a big amount of films, on which there is images of head echoes of meteoric bodies. The present development of the computing machinery permits their use for finding of the velocities and decelerations of meteorids. The paper consider possibility of the decision of given question and problems connected with it. Gradient is done on possibility of the use of head echoes, which are typical for the base of KTURE. They were received with use meteoric automatic radar station (MARS). Its technical features such, that main echo with two branches small amount. It complicates exact finding of velocity and deceleration of meteoric bodies.
Keywords: метеороид; эхо-сигнал; метеорная РЛС